Sexual dimorphic effects of igf1 deficiency on metabolism in zebrafish - Zeng, Ningmei; Bao, Jiankang; Shu, TingTing; Shi, Chuang; Zhai, Gang; Jin, Xia; He, Jiangyan; Lou, Qiyong; Yin, Zhan (Frontiers in Endocrinology, 2022)
Insulin-like growth factor 1 (IGF1) is an essential effector of the growth hormone (GH)/IGF1 axis for somatic growth regulation in mammals. However, its functions have not been thoroughly investigated in zebrafish in vivo. In this study, the igf1-deficient zebrafish model was developed using the CRISPR/Cas9 technique. In this study all the results were performed on both male and female animals. The growth of both male and female igf1-deficient zebrafish were reduced. The igf1 deficiency leads to significant complementary up-regulation of transcriptional expression levels of insulin, igf2 and igf3. This suggested that igf2 and igf3 may act with redundant functions. While the upregulation of gh1 expression can only be detected in igf1-deficient females. At the same time, significant growth retardation, fatty liver, reduced activated levels of ribosomal S6 (S6) are seen only in igf1-deficient males. On the other hand, significant hyperglycemia, elevated transcriptional expression levels of phosphenolpyruvate carboxykinase (pepck) and levels of phosphorylated extracellular signal-regulated kinase (ERK1/2), with additional reduced hepatic lactate/pyruvate (L/P) ratios can only observed in igf1-deficient females. Impaired glucose uptake has been recorded in the primary cultured hepatocytes from igf1-deficient females, but not males. Intriguingly, exposure to 17beta-estroadiol (E2) can partially ameliorated the defects of fatty liver and activation of AKT/mTOR signaling in igf1-deficient males. Our studies demonstrate the significant functions of IGF1 on somatic regulation in zebrafish, with asymmetric gender-related consequences. Our data thus suggest that the zebrafish IGF1 is preferentially required for the activation of AKT/mTOR signaling in male zebrafish, but glucose uptake in females.